Pengembangan Lembar Kerja Siswa Berbasis Literasi Sains pada Materi Alat-Alat Optik untuk Meningkatkan Kemampuan Literasi Sains Siswa SMP (UPEJ Unnes Physics Education Journal, 2020)
The objectives of this research are describe the characteristics, determine the validity, to test the practicality of worksheet based on scientific literacy, and to test the effectiveness of the product in improving studentâ€™s scientific literacy capability. The type of this research is Research and Development (R&D) that produces worksheet based on scientific literacy on optical tools topics. The research was done at SMP Rembang, Purbalingga. The characteristics of the worksheet which is developed are using four scientific literacy aspects that can be found in the worksheet main feature, that are â€œAyo Belajarâ€, â€œMencoba Yukâ€, â€œAyo Berpikir Ilmiahâ€, and â€œSains dalam Kehidupanâ€. The research findings shows that the validity testâ€™s result of the worksheet is in valid category with the result of 84.95%. The result of practicality of the worksheet based on scientific literacy is in the practical category with the result of 82.60%. The improvement of scientific literacy capability in cognitive aspect showed that the experimental class was 0.69 and the control class was 0.47. The result showed that affective and psychomotoric learning in the experimental class is higer than the control group. Based on the result, it is concluded that the worksheet based on scientific literacy is valid, practical, and effective to increase studentâ€™s scientific literacy capability.